OCEAN MODELLING IN BRAZIL, A QUICK OVERVIEW: Modelagem oceânica no Brasil, uma visão geral rápida - Marta-Almeida, Martinho (Arquivos de Ciências do Mar, 2022)
Hydrodynamic numerical modelling studies, at least partially focused on the Brazilian oceanography, were identified using the Scopus database. Ocean modelling in Brazil started in 1994 and has been increasing especially since 2007. In recent years, however, the rate of the increase is slowing. The main ocean models used are ROMS, POM and HYCOM, and the main institutions publishing in ocean modelling in Brazil are located in the states of São Paulo and Rio de Janeiro, resulting in the Southeast as the most studied region. Men dominate the ocean modelling in Brazil, with only three women in the top twenty scientists. Oil industry is a great sponsor of oceanography in Brazil. The interest in renewable energy offshore is, on the other hand, very low, with only two publications assessing the potential for renewable energy extraction from the ocean. Keywords: ocean modelling, Brazil, models, regions, authors.